Cluster of Burkholderia cepacia Complex Infections Associated With Extracorporeal Membrane Oxygenation Water Heater Devices . (10th March 2022) - Rhee, Chanu; Baker, Meghan A; Tucker, Robert; Vaidya, Vineeta; Holtzman, Meghan; Seethala, Raghu R; Bentain-Melanson, Maria; Lenox, Jesslyn; Smith, Adam R; Boyer, Jon C; Gassett, Alison; Brigl, Manfred; et al.
Abstract: Background: Burkholderia cepacia complex is a group of potential nosocomial pathogens often linked to contaminated water. We report on a cluster of 8 B. cepacia complex infections in cardiothoracic intensive care unit patients, which were attributed to contaminated extracorporeal membrane oxygenation (ECMO) water heaters. Methods: In December 2020, we identified an increase in B. cepacia complex infections in the cardiothoracic intensive care unit at Brigham and Women's Hospital. We sought commonalities, sequenced isolates, obtained environmental specimens, and enacted mitigation measures. Results: Whole-genome sequencing of 13 B. cepacia complex clinical specimens between November 2020 and February 2021 identified 6 clonally related isolates, speciated as Burkholderia contaminans . All 6 occurred in patients on ECMO. Microbiology review identified 2 additional B. contaminans cases from June 2020 that may have also been cluster related, including 1 in a patient receiving ECMO. All 8 definite or probable cluster cases required treatment; 3 patients died, and 3 experienced recurrent infections. After ECMO was identified as the major commonality, all 9 of the hospital's ECMO water heaters were cultured, and B. contaminans grew in all cultures. Cultures from air sampled adjacent to the water heaters were negative. Water heater touch screens were culture positive for B. contaminans, and the sink drain in the ECMO heater reprocessing room also grew clonal B. contaminans. Observations of reprocessing revealed opportunities for cross-contamination between devices through splashing from the contaminated sink. The cluster was aborted by removing all water heaters from clinical service. Conclusions: We identified a cluster of 8 B. cepacia complex infections associated with contaminated ECMO water heaters. This cluster underscores the potential risks associated with water-based ECMO heaters and, more broadly, water-based care for vulnerable patients. Abstract : We identified a cluster of 8 Burkholderia cepacia complex infections associated with contaminated extracorporeal membrane oxygenation (ECMO) water heaters. This cluster underscores the potential risks associated with water-based ECMO heaters and, more broadly, water-based care for vulnerable patients.